Respuesta :

Answer:

4x + 4

Step-by-step explanation:

F(x) = 2x - 1

G(x) = 3x + 2

H(x) = x²

We have to calculate the expression F(G(x)) - F(x)

F(G(x)) means the composition of functions F(x) and G(x). In order to find F(G(x)) we have to replace ever occurrence of x in F(x) with the value of G(x). So,

F(G(x)) = 2(3x+2) - 1 = 6x + 4 - 1 = 6x + 3

Thus,

F(G(x)) - F(x) = 6x + 3 - (2x - 1)

= 6x + 3 -2x + 1

= 4x + 4

Therefore, the expression F(G(x)) - F(x) equals 4x + 4

ACCESS MORE
EDU ACCESS